Fruit traits of pioneer trees structure seed dispersal across distances on tropical deforested landscapes: Implications for restoration - Camargo, Paulo H. S. A. [UNESP]; Pizo, Marco A. [UNESP]; Brancalion, Pedro H. S.; Carlo, Tomás A. (Wiley, 2020)
Pioneer trees with fleshy fruits are typically planted in restoration projects to attract frugivores as a mean to increase dispersal and accelerate forest regeneration. However, differences in fruit traits of pioneer trees can potentially influence dispersal and their restoration outcomes. Here we investigated the effects of bird and plant traits, and distance to forest fragments, on the seed rain using a tree-planting experiment replicated in 12 deforested sites in Brazil. Factors were fruit traits of pioneer trees (wind-dispersed, bird-dispersed with lipids or with carbohydrates and controls) and distance (10, 50, 300 m) from forest fragments. We found that density and richness of birds and seeds decreased exponentially with distance from fragments, yet these effects were minor compared to the effects of fruit traits on the structure of the seed rain. Overall, plots with fleshy fruited pioneers attracted much greater bird activity and seed dispersal than plots with wind-dispersal pioneers and the controls. For instance, plots with carbohydrate-rich fruits received more than twice the average species richness and density of birds and seeds of plots with lipid-rich pioneer trees, surpassing wind-dispersed pioneers by more than 80%, and controls by over 90%. Furthermore, the fruit trait treatments resulted in morphological shifts in the average traits of visiting birds. Significant differences in bill gape and flight capacities (wing-loading) were associated with the differences in the seed rain associated with each treatment. Synthesis and applications. Understanding how trait-matching processes mediating mutualistic seed dispersal by frugivores interact with distance-dependent dispersal limitation on deforested tropical landscapes is critical for improving forest restoration efforts. This is especially relevant in the context of applied nucleation. As shown here, avian seed dispersal can thus be manipulated in restoration projects in order to increase connectivity and speed up forest recovery and the provision of the multiple ecosystem services that follow forest succession.
Keywords: applied nucleation; connectivity; forest restoration; frugivory; fruit chemical content; long-distance seed dispersal; planting; trait-matching